MICRONUCLEUS TEST AS AN INDICATOR OF ORGANOCHLORINE PESTICIDES EFFECT (Proceedings of the YSU B: Chemical and Biological Sciences, 2023)
The micronucleus (MN) level in exfoliated buccal mucosa cells of women from Yerevan and Aragatsotn region of RA was observed. The results revealed that the MN level in two studied groups didn’t show statistically significant increase during the investigated periods (2005 and 2006). Nevertheless, the tendency of increased level of MN was observed in women from villages.
Keywords: micronucleus; women; exfoliated buccal mucosa cells